2015
DOI: 10.1186/s12864-015-1626-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the neurotranscriptomic states in alternative stress coping styles

Abstract: BackgroundAnimals experience stress in many contexts and often successfully cope. Individuals exhibiting the proactive versus reactive stress coping styles display qualitatively different behavioral and neuroendocrine responses to stressors. The predisposition to exhibiting a particular coping style is due to genetic and environmental factors. In this study we explore the neurotranscriptomic and gene network biases that are associated with differences between zebrafish (Danio rerio) lines selected for proactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(98 citation statements)
references
References 76 publications
(101 reference statements)
2
94
0
1
Order By: Relevance
“…exploratory behavior) in an open field test and were 10 generations removed from a wild caught population from Gaighata in West Bengal, India 41 . The HSB and LSB strains display behaviors across multiple different behavioral assays, glucocorticoid responses, and morphology consistent with the reactive and proactive stress coping styles, respectively 31,41,45,53,54 . Additionally, HSB and LSB strains differ in neurotranscriptome profiles 54,55 .…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…exploratory behavior) in an open field test and were 10 generations removed from a wild caught population from Gaighata in West Bengal, India 41 . The HSB and LSB strains display behaviors across multiple different behavioral assays, glucocorticoid responses, and morphology consistent with the reactive and proactive stress coping styles, respectively 31,41,45,53,54 . Additionally, HSB and LSB strains differ in neurotranscriptome profiles 54,55 .…”
Section: Methodsmentioning
confidence: 90%
“…The HSB and LSB strains display behaviors across multiple different behavioral assays, glucocorticoid responses, and morphology consistent with the reactive and proactive stress coping styles, respectively 31,41,45,53,54 . Additionally, HSB and LSB strains differ in neurotranscriptome profiles 54,55 . Females of both strains exhibit higher stationary time than males in an open field test 41,56 .…”
Section: Methodsmentioning
confidence: 90%
“…Among the questions raised are: via what mechanisms are trait correlations inherited, which circumstances benefit different complex phenotypes, and what are the costs and benefits of the limited plasticity imposed by fixed trait associations? In the bioinformatics era, it should also be noted that understanding individual variation may be of vital importance for the interpretation of transcriptomic data [see for example Crawford and Oleksiak, 2008;MacKenzie et al, 2009;Wong et al, 2015;Rey et al, 2016].…”
Section: Neurogenesis In Fishmentioning
confidence: 99%
“…LSB animals display less anxiety-like behaviour in the novel tank test and light/dark test, a lower fear-like behaviour during alarm substance exposure, lower latency to feed after a disturbance, and a higher probability of orienting towards a human observer than HSB animals (Wong et al, 2012). 62 genes were found to be upregulated in the brains of proactive (LSB) animals, including genes involved in the biosynthesis and metabolism of organic acids, carboxylic acids, and fatty acids (Wong et al, 2015). The authors suggested that these differences could be related to dealing with oxidative stress expression of the methylsterol monoxygenase-coding gene msmo1 and 11β-hydroxysteroid dehydrogenase-coding gene hsd11b2, and negatively correlated with gabbr1a expression, a gee which codes for the GABAB receptor.…”
Section: Coping Mechanisms and Monoamines In Fishmentioning
confidence: 99%